1995
DOI: 10.3164/jcbn.19.79
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Studies Evaluating the Antiulcerogenic Potential of Ocimum sanctum in Experimentally Induced Peptic Ulcers in Rats.

Abstract: SummaryThe effect of pretreatment with Ocimum sanctum, an herbal drug, on HCl-ethanol-induced gastric lesions in rats was investigated with respect to acid/pepsin, lipid peroxidation, antioxidant status, and glycoproteins in the gastric mucosa. The increase in volume and acidity of the gastric juice and the decrease in peptic activity in HClethanol-exposed mucosa were maintained at near normalcy in O. sanctum-pretreated mucosa. The increase in lipid peroxidation, decrease in activity of antioxidants in the ulc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…This indicated that administration of ibuprofen caused the corrosion of gastric mucosa, resulting in the disruption and disintegration of gastric mucosal cells. Similar observations have been reported earlier 22 . The ulcerative lesions observed in the gastrointestinal tract may also be associated with increased loss of protein.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This indicated that administration of ibuprofen caused the corrosion of gastric mucosa, resulting in the disruption and disintegration of gastric mucosal cells. Similar observations have been reported earlier 22 . The ulcerative lesions observed in the gastrointestinal tract may also be associated with increased loss of protein.…”
Section: Discussionsupporting
confidence: 90%
“…Similar observations have been reported earlier. 22 The ulcerative lesions observed in the gastrointestinal tract may also be associated with increased loss of protein. According to Davenport's concept of H + release, histamine stimulates cholinergic nerves with a resulting stimulation of acid secretion, an increase in mucosal blood flow, and an increase in capillary permeability.…”
Section: Discussionmentioning
confidence: 99%